The Effect of Age and Education Level as a Source of Information on Internet Use in Preoperative Patients - Yasin Tire; Eyüp Aydoğan; Abdullah Celep; Aydın Mermer (Baiman Bauntung Batuah Center, 2020)
Most patients rely on the internet to access a medical information source. Patients undergoing surgery use the internet and social media to gain information about anesthesia and surgery. In our study, it has dealt with the use of the internet and social media for news in patients who will undergo surgery and the impact of age and education on this situation. Every patient who came to our clinic for surgery between August 1, 2019 and December 31, 2019 was asked to complete a survey preoperatively. This questionnaire includes questions about internet use. The rate of using the internet as the source of anesthesia information was 24.3% in young patients, this rate found to be 7% in the middle age patients, and none of the elderly patients used the internet as the source of anesthesia information. In terms of operation information, the rate of those using internet as a source of information in the young patients was 29.7%, whereas it was 14% in the middle age patients, and the rate was 5.3% in the elderly patients. Some of the patients (21%) who came to the clinic used internet and social media as a source of information. This study has been found useful in the sense that anesthesiologists and surgeons send information about themselves on the internet and be accessible via social media.